Anti-kelch-like protein 11 antibody-associated encephalitis: two case reports and literature review - Shuting Chai; Gang Liu; Yan Zhang (BMC Neurology)
Abstract Background Anti-kelch-like protein 11 (KLHL11) antibody-associated encephalitis is a rare autoimmune neurological disorder, typically presenting with cerebellar syndrome and brainstem involvement. Diagnosis relies on the detection of anti-KLHL11 antibodies in serum and/or cerebrospinal fluid (CSF). Immunotherapy remains the cornerstone of treatment. Case presentation Patient 1 presented with an acute onset of dizziness, limb weakness, and slowed responses, with rapid symptom progression. Despite receiving immunotherapy—including intravenous corticosteroids, immunoglobulin, plasma exchange, and efgartigimod—which resulted in partial improvement, the patient experienced a rapid relapse and further clinical deterioration. He ultimately succumbed to central circulatory failure. Patient 2 exhibited a relatively slow disease course, primarily characterized by gait disturbances, slurred speech, and memory decline. He received only symptomatic treatment without immunotherapy. Follow-up assessments indicated slight symptomatic improvement. Brain magnetic resonance imaging (MRI) showed multiple hyperintense lesions on T2-weighted fluid-attenuated inversion recovery (T2/FLAIR) in the bilateral subcortical cerebral hemispheres and pons in patient 1. However, dominant pontine and cerebellar atrophy were noted in patient 2. Initial serum cell-based assay (CBA) testing detected anti-KLHL11 antibody titers of 1:30 in patient 1 and 1:100 in patient 2. Conclusion This study indicates that patients with KLHL11-IgG encephalitis may present not only with typical cerebellar symptoms, such as ataxia, and brainstem signs, such as dysarthria, but also with rapidly progressive impairment of consciousness accompanied by seizures. The differences in disease course and MRI findings observed between the two patients further suggest that clinical and imaging heterogeneity may be related to disease chronicity. Therefore, it is essential to recognize the diverse clinical presentations and varying stages when diagnosing KLHL11-IgG encephalitis. For patients exhibiting such symptoms, after exclusion of other potential causes, timely KLHL11-IgG antibody testing and tumor screening are recommended to facilitate early diagnosis and prompt treatment, thereby improving prognosis.